Transbronchial cryobiopsy increases diagnostic confidence in interstitial lung disease: a prospective multicentre trial - Hetzel, Jürgen; Kreuter, Michael; Eberhardt, Ralf; Warth, Arne; Heußel, Claus Peter (The European respiratory journal, 2020)
Introduction The accurate diagnosis of individual interstitial lung diseases (ILD) is often challenging, but is a critical determinant of appropriate management. If a diagnosis cannot be made after multidisciplinary team discussion (MDTD), surgical lung biopsy is the current recommended tissue sampling technique according to the most recent guidelines. Transbronchial lung cryobiopsy (TBLC) has been proposed as an alternative to surgical lung biopsy. - Methods This prospective, multicentre, international study analysed the impact of TBLC on the diagnostic assessment of 128 patients with suspected idiopathic interstitial pneumonia by a central MDTD board (two clinicians, two radiologists, two pathologists). The level of confidence for the first-choice diagnoses were evaluated in four steps, as follows: 1) clinicoradiological data alone; 2) addition of bronchoalveolar lavage (BAL) findings; 3) addition of TBLC interpretation; and 4) surgical lung biopsy findings (if available). We evaluated the contribution of TBLC to the formulation of a confident first-choice MDTD diagnosis. - Results TBLC led to a significant increase in the percentage of cases with confident diagnoses or provisional diagnoses with high confidence (likelihood ≥70%) from 60.2% to 81.2%. In 32 out of 52 patients nondiagnostic after BAL, TBLC provided a diagnosis with a likelihood ≥70%. The percentage of confident diagnoses (likelihood ≥90%) increased from 22.7% after BAL to 53.9% after TBLC. Pneumothoraces occurred in 16.4% of patients, and moderate or severe bleeding in 15.7% of patients. No deaths were observed within 30 days. - Interpretation TBLC increases diagnostic confidence in the majority of ILD patients with an uncertain noninvasive diagnosis, with manageable side-effects. These data support the integration of TBLC into the diagnostic algorithm for ILD. - Tweetable abstract ERSpublications - click to tweetTransbronchial cryobiopsy increases diagnostic likelihood of the first-choice diagnosis and confirms specified ILD diagnosis in a clinically relevant number of patients https://bit.ly/3hmd7HX
Gesehen am 03.11.2021